Unveiling the Correlation Between Thyroid Dysfunction and Post-Surgical Septicemia in Geriatric Patients - Rain, Pallavi; Batra, Jyoti; Batra, Ankit; Batra, Aarushi (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Background and Aim: Sepsis is a life-threatening issue that happens when the body’s immune system has an extreme response to an infection, causing organ dysfunction. Critical illness and sepsis are difficult to treat with increasing age because of the poor adaptive physiological system as age progresses. The study tries to identify prognostic markers among thyroid hormones for post-surgical critically ill subjects, who have sepsis, to improve the outcome of patients with increasing age. Methods: Post-surgical critically ill patients with sepsis were recruited in the study. Key features of the critically ill patient are severe respiratory, cardiovascular or neurological derangement, often in combination, reflected in abnormal physiological observations. Free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) were estimated by ARCHITECT immunoassay kits in 127 post-surgical critically ill patients with sepsis. Sequential Organ Failure Assessment (SOFA) score was recorded for each patient. Results: The FT3, FT4 and TSH levels decreased and SOFA scores increased with increasing age. Thyroid markers were significantly inversely correlated with age (for FT4 r= -0.616, p<0.0001 and for TSH r= -0.453, p<0.0001), with the strongest correlation between FT3 and age (r=0.674, p<0.0001). A positive correlation was observed between SOFA score and age (r=0.577, p<0.0001). FT3 decreases SOFA and age increase from improved prognosis to worst prognosis (p<0.0001). The patients whose condition improved were mostly young as compared to the no change group, deteriorated group and expired group. Conclusions: FT3 surfaced as a prominent prognostic marker that may be used in predicting the prognosis of post-surgical critically ill geriatric patients with sepsis.